Effect of Clinical and Histological Chorioamnionitis on the Outcome of Preterm Infants - Nasef, Nehad; Shabaan, Abd Elazeez; Schurr, Patti; Iaboni, Dolores; Choudhury, Julie; Church, Paige; Dunn, Michael S. (American Journal of Perinatology, 2013)
Chorioamnionitis contributes to neonatal and maternal morbidity and mortality. We aimed to evaluate of the impact of clinical and histological chorioamnionitis on mortality and morbidity of preterm infants. Maternal and neonatal data were collected in a retrospective cohort of preterm infants less than 30 weeks' gestation. Infants were divided into three groups: those born to mothers with clinical chorioamnionitis, histological chorioamnionitis, or no chorioamnionitis. Of 274 identified preterm infants, 33 infants were born to mothers with clinical chorioamnionitis, 95 to mothers with histological chorioamnionitis, and 146 to mothers with no chorioamnionitis. Data were available for 180 (78%) of the 230 survivors at 18 months corrected age. Infants in the study groups were similar in gestational age, birth weight, and sex distribution. Clinical and histological chorioamnionitis were not predictive of infant mortality, cerebral palsy, bronchopulmonary dysplasia, periventricular leukomalacia, or retinopathy of prematurity. Infants in the clinical chorioamnionitis group had significantly lower cognitive (88 ± 10), language (82 ± 12), and motor (89 ± 11) scores compared with infants in the histological chorioamnionitis group (101 ± 13, p < 0.01; 91 ± 13, p < 0.05; and 99 ± 13, p < 0.05, respectively) and to infants in the no chorioamnionitis group (99 ± 13, p < 0.01; 92 ± 15, p < 0.05; and 97 ± 13, p < 0.05, respectively). Clinical chorioamnionitis is associated with developmental delay in preterm infants despite adequate treatment.
Keywords: chorioamnionitis; preterm infants; perinatology; neurodevelopment